Optimizing Photovoltaic Array Performance Under Partial Shading Using a Golden Ratio-Based Configuration: A Comparative Analysis of 16 Configurational Variants - Sakthivel Ganesan; Prince Winston David; Hariharasudhan Thangaraj; Devakirubakaran Samithas; Praveen Kumar Balachandran; Muhammad Ammirrul Atiqi Mohd Zainuri (IEEE Access)
The growing need for generation of electric power because of increasing energy consumption requires the need of renewable energy sources. Solar photovoltaic (PV) systems are suitable solution to this issue, however its efficiency might decrease under partial shade conditions. In this work, we propose a new array configuration for a $4× 4$ solar PV array under different partial shading environments. We validate the proposed method by testing 18 different shading patterns that our configuration greatly increases power output, lowers mismatch losses, and improves the fill factor relative to traditional techniques. Comparatively to the conventional Total cross-Tied (TCT) method’s 68 W and fill factor of 0.29, proposed method achieves a power output of 76 W, a reduction in mismatch losses to 15%, and a fill factor of 0.32 under diagonal and long partial shading. The proposed produces a maximum power output of 88 W for inverse diagonal conditions, effectively lowering power losses by 20%. With up to a 12% increase in power output and a 15% decrease in mismatch losses under several shading conditions, the proposed configuration consistently outperforms conventional techniques. This proposed method offers an effective solution for improving power generation under abnormal conditions and shows significant improvement in PV array optimization.